Trial and error, together: divergent thinking and collective learning in the implementation of integrated care networks. (September 2018) - Evans, Jenna M.; Grudniewicz, Agnes; Tsasis, Peter
Hybrid networks that link disparate professionals and organizations are a common approach to deliver integrated care to patients. Recent literature argues that successful implementation of these networks demands a socio-cognitive perspective in which stakeholder mental frames and thought processes are prioritized, investigated, and compared. The aims of this article are to identify where mindsets diverge among clinical and managerial stakeholders involved in the implementation of integrated care networks known as 'Health Links' (HLs) in Ontario, Canada, and to describe strategies to support stakeholders' capacity to collectively learn and develop more convergent views. Drawing from shared mental model theory and practice-based learning theory, a secondary analysis was conducted of interview data with 55 healthcare professionals and managers involved in the implementation of HLs. We identified examples of divergences in stakeholders' conceptualization of the HL design and approach ('strategy mental model') and their perceptions of each other and how they work together ('relationship mental model'). We also identified four strategies that facilitate learning and possibly mental model convergence. The results of the study may help guide stakeholder dialogue towards collective learning and coordinated action for integrated care delivery. Points for practitioners: The findings suggest that in the implementation of large-scale change involving multiple stakeholder groups, there are predictable areas where divergent views are likely to occur and may have a negative impact on coordinated action. An awareness of these potential divergences can guide practitioners to examine them explicitly and regularly, and to proactively develop strategies to support practice-based learning and the development of a convergent perspective.